ESRD POST-HOSPITALIZATION ANEMIA AND ESA UTILIZATION - Alex Yang; Will Harrison; Ali Hariri (The Korean Society of Nephrology, 2012)
On average ESRD patients are hospitalized twice yearly for 12 days a year (USRDS 2011 Ann. Report). Hb levels decline immediately post-hospitalization, requiring extended periods for recovery and elevated ESA dosing for >1 year (Solid et al. Hemodial Int. 2007). We evaluated post-hospitalization anemia trends and ESA use in ESRD. Data from an LDO (N=273,877 pts; Q1 2008-Q1 2011) were evaluated for post-hosp Hb change (difference, pre- and post-hosp Hb measurement), time to Hb recovery (time from discharge to when Hb levels ≥ pre-hosp level), time to ESA recovery (time from discharge until 3 consecutive non-zero epoetin doses ≤ pre-hosp dose) and incremental ESA (sum of all differences from last pre-hosp dose until ESA recovery, 6 months if no recovery, or end of follow-up for long-term follow-up population). 62% of all hospitalizations were associated with declining Hb (mean, -1.29 g/dL; Figure); 54% of these never returned to pre-hosp levels. Among hospitalizations that experienced a Hb drop and eventually recovered Hb (mean recovery time, 42 days), 73% used a mean 56K U of incremental epoetin until recovery; dose was recovered within 68 days on average. For the remaining 27% who never returned to pre-hosp ESA dose, an additional 266K U of epoetin were utilized. The majority of hospitalizations (∼2/3) had considerable post-hosp Hb drops (mean >1g/dL), with >50% permanently reduced. ∼1.5 months were needed to recover Hb, with elevated ESA doses for >2 months. ESA dose was permanently elevated in 27% of hospitalizations that recovered Hb. Strategies to address post-hosp anemia may mitigate the protracted recovery time and increased ESA use. fx1